2017
DOI: 10.1080/09585176.2016.1261718
|View full text |Cite
|
Sign up to set email alerts
|

Should we embed careers education in STEM lessons?

Abstract: Schools have a particular responsibility to introduce young people to the range of possible options for them after they leave education as few families can provide this. However, in the United Kingdom, careers education is currently not strong in most schools for a number of reasons but principally due to its low status and shifts in government policy and funding. As a result, too many young people make subject choices for post‐16 study that they subsequently regret. In particular, fewer young people in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…However, it can be said that the STEM approach has a positive contribution to students' STEM career interests in general. In the literature, this finding is consistent with the study of Reiss and Mujtaba (2017), in which they emphasize the importance of integrating career education into STEM courses. Furthermore, Franz-Odendaal, Blotnicky, French and Joy (2016), emphasize in their study that the participation of the students in STEM activities significantly and positively influenced their attitudes towards STEM field careers, which supports the findings of our study.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 81%
“…However, it can be said that the STEM approach has a positive contribution to students' STEM career interests in general. In the literature, this finding is consistent with the study of Reiss and Mujtaba (2017), in which they emphasize the importance of integrating career education into STEM courses. Furthermore, Franz-Odendaal, Blotnicky, French and Joy (2016), emphasize in their study that the participation of the students in STEM activities significantly and positively influenced their attitudes towards STEM field careers, which supports the findings of our study.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 81%
“…They attributed this result to girls' higher outcome expectations toward science learning, which predicted career goals much more than self-concept did in Finland. In line with Kang and Keinonen (2017), Reiss and Mujtaba (2017) also reported that extrinsic motivation in physics was the most important predictor of students' intention to study physics after the age of 16, more than any other factors such as interest or self-concept.…”
Section: Early Aspirations Toward Science Education and Careersmentioning
confidence: 58%
“…However, this early-career expectation in science increases the probability of earning a higher degree in science and engineering at university (Tai et al 2006). In the early stage, constructs of aspirations of studying advanced science and pursuing science careers are not separable, since many students choose their science subjects with career choices in mind (Reiss and Mujtaba 2017); that is, young students understand that their subject choices at school are important steps on the path to achieving their career aspirations in future. Thus, science aspirations at this age are "understood as students' desire to pursue science further in their schooling and as a potential career path" (DeWitt et al 2013, p. 1038).…”
Section: Early Aspirations Toward Science Education and Careersmentioning
confidence: 99%
“…The findings showed that the students developed comprehensive understandings about the experts' background, skills, and tasks, especially in relation to the science concepts introduced in each scenario. Reflecting on this finding, there seems to be a clear argument that career-related information can be induced productively in science class, reinforcing Reiss and Mujtaba's (2017) suggestion to embed careers education in STEM lessons. Nevertheless, as the findings also revealed, solely providing career-related information, albeit in personally relevant and meaningful ways, did not result in more students interested in exploring the possibility to pursue STEM careers.…”
Section: Developing Understandings Of Stem Careersmentioning
confidence: 79%